Rock’n’roll, drugs, stigmas and risks - Martins, Ana (2021)
This article tries to explore the applicability of the epitome ‘Sex, drugs and rock’n’roll’ to the Portuguese social reality, particularly in the field of rock music. Rock music took its first steps in Portugal in the late 1950s/early 1960s, and from an early age, it has been associated with risky conducts, particularly linked to sex, alcohol, and the use of other licit and illicit substances. So, in the same way that happened in the Anglo-Saxon reality, this epitome encloses a vast process of moral panic production/reproduction in Portugal. Considering the absence of scientific research exploring the association between rock music, substance use and/or abuse and occasional and/or risky sexual conducts in Portugal, we consider it crucial to develop this approach. This article is based on factual and current data, particularly interviews from some protagonists of the Portuguese rock music scene.